2002
DOI: 10.1089/08977150260139138
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glutathione Augmentation on Lipid Peroxidation after Spinal Cord Injury

Abstract: Lipid peroxidation (LPO) is considered a major factor in damage spread after spinal cord injury (SCI). Therapies that limit LPO after SCI have demonstrated some utility in clinical trials, but more effective treatments are needed. In the present study the effects of augmenting SC levels of the endogenous antioxidant glutathione (GSH) on LPO after SCI were studied in a rat contusion injury model. A significant decrease in GSH occurred 1h after SCI which was paralleled by increases of 123% in malondialdehyde (MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 47 publications
4
31
0
2
Order By: Relevance
“…Others have confirmed that MDA levels increase in the first 2 h [15]. An increase in LP that appears in the injured cord within the first hour has also been evidenced in terms of a depletion of endogenous antioxidants, including ascorbic acid [16], alpha-tocopherol (also known as vitamin E) [17], glutathione [18], and ubiquinol-9 and ubiqunol-10 [19]. More contemporary immunohistochemical and immunoblotting methods have been recently used, which reveals an impressive increase in the levels of the LP-derived aldehydic breakdown products 4-HNE [20][21][22][23] and acrolein [24,25].…”
Section: Increased Lipid Peroxidationmentioning
confidence: 92%
See 2 more Smart Citations
“…Others have confirmed that MDA levels increase in the first 2 h [15]. An increase in LP that appears in the injured cord within the first hour has also been evidenced in terms of a depletion of endogenous antioxidants, including ascorbic acid [16], alpha-tocopherol (also known as vitamin E) [17], glutathione [18], and ubiquinol-9 and ubiqunol-10 [19]. More contemporary immunohistochemical and immunoblotting methods have been recently used, which reveals an impressive increase in the levels of the LP-derived aldehydic breakdown products 4-HNE [20][21][22][23] and acrolein [24,25].…”
Section: Increased Lipid Peroxidationmentioning
confidence: 92%
“…Although this tripartite LOO• antioxidant defense system (vit E, vitamin C, GSH) works fairly effectively in the absence of a major post-traumatic oxidative stress, studies have shown that each of these antioxidants is rapidly consumed during the early minutes and hours after SCI [16][17][18]. Thus, it has long been recognized that more effective pharmacological LOO• and LO• scavengers are needed than what endogenous biochemistry has provided.…”
Section: Overview Of Antioxidant Mechanistic Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Lucas,et al 14 examined the effects of glutathione treatment on lipid peroxidation after SCI in a rat contusion injury model. The results suggested that elevation of levels of glutathione by irrigation with d-glutamylcysteine conferred significant protection against lipid peroxidation after SCI, suggesting that glutathione augmentation may be an effective strategy for curtailment of lipid peroxidation-mediated damage in SCI.…”
Section: Ros and Oxidative Stress In Scimentioning
confidence: 99%
“…The results suggested that elevation of levels of glutathione by irrigation with d-glutamylcysteine conferred significant protection against lipid peroxidation after SCI, suggesting that glutathione augmentation may be an effective strategy for curtailment of lipid peroxidation-mediated damage in SCI. 14 Mutations in the gene for Cu,ZnSOD have been identified in familial amyotrophic lateral sclerosis (ALS), a disease characterized by damage and loss of neurons in both the brain and the spinal cord. 15 Transgenic mice overexpressing wide-type Cu,ZnSOD gene show resistance to SCI, indicating that Cu,ZnSOD has an important role in protecting against spinal neuron death.…”
Section: Ros and Oxidative Stress In Scimentioning
confidence: 99%